Tears in the Graeco-Roman World 2009
DOI: 10.1515/9783110214024.439
|View full text |Cite
|
Sign up to set email alerts
|

Crying: A Biopsychosocial Phenomenon

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercial gain-You may freely distribute the URL identifying the publication in the public portal Take down policy If you believe that this document breaches copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 74 publications
3
55
1
Order By: Relevance
“…Crying has been a topic of growing interest for several years (Kottler, 1996;Nelson, 1998Nelson, , 2005Nelson, , 2008Vingerhoets, 2013;Vingerhoets & Cornelius, 2012;Vingerhoets, Cornelius, Van Heck, & Becht, 2000;Vingerhoets, Van Geleuken, Van Tilburg, & Van Heck, 1997). Clients report that crying in session has improved their relationship with their therapist (Zingaretti et al, 2017), but it is unclear how therapists' in-session tears impact the psychotherapy process.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crying has been a topic of growing interest for several years (Kottler, 1996;Nelson, 1998Nelson, , 2005Nelson, , 2008Vingerhoets, 2013;Vingerhoets & Cornelius, 2012;Vingerhoets, Cornelius, Van Heck, & Becht, 2000;Vingerhoets, Van Geleuken, Van Tilburg, & Van Heck, 1997). Clients report that crying in session has improved their relationship with their therapist (Zingaretti et al, 2017), but it is unclear how therapists' in-session tears impact the psychotherapy process.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…Although this idea has some empirical support (Frey, Hoffman-Ahern, Johnson, Lykken, & Tuason, 1983;, more recent research has suggested that this may not be the case. Rather, Vingerhoets and Cornelius (2012) proposed the notion that men may not actually be brought to tears less often; they suggested what might be happening is that they are "swallowing" their tears more often than women. If this norm were to apply to a therapy context, we would expect to see either fewer male therapists reporting crying in session or more reports of male therapists suppressing their tears.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…In 1901, Patrick [ 2 ] concluded that swearwords are primarily used by soldiers, sailors, laborers, uneducated people, and criminals, and men make up the majority of these social groups. While swearing has been considered a predominately masculine activity, women now tend to swear as much, or even more often, then men [ 3 ]. Since swearing is considered taboo, these words are usually judged as shocking, and the swearer may be considered antisocial and offensive.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have been swearing since the emergence of language [ 3 ] and is quite common, with evidence suggesting 58% of the population swears “sometimes” or “often” and less than 10% of the population report “never” or “rarely” swearing [ 8 ]. Most often, it is the swear word itself that is considered taboo rather than the semantic meaning it conveys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation